Rachunkowość rolnicza i jej przydatność w procesie podejmowania decyzji w gospodarstwie - Łapińska, Anna; Zabielska, Daniela (Agricultural Accountancy and Its Usefulness in the Decision Taking Process at a Farm, 2005)
Accountancy and economics analysis have a special place among the basic sources of information necessary for good management practice at an agricultural farm. Financial reporting and ratios analysis play an important role. It is useful to make comparisons of the results achieved with ratios achieved by other farms representing a similar economic potential.The research aims at identifying the usefulness of agricultural accountancy for decision taking at agricultural farms. Farms maintaining accountancy according to the Uniform System of Agricultural Farms Accountancy (ZSRGR), situated in the country of Łomża have been chosen for the analysis. Those farms have been selected on purpose as farms that were required to have main full accountancy and which benefited from preferential loans.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 31-37